An Acyclic Arsenium Cation Stabilised by a Single P–As π‐Interaction and a Cyclic Diphosphinophosphonium Salt. Issue 32 (3rd July 2019) - Izod, Keith; Evans, Peter; Waddell, Paul G.
Abstract: Stable acyclic arsenium cations R2 As +, isoelectronic analogues of germylenes, are rare in comparison to the corresponding phosphenium cations. The first example of a diphosphaarsenium salt, [(Dipp)2 P2 As][AlOC(CF3 )3 4 ]⋅1 1 / 2 PhMe, is described. This salt exhibits remarkable stability due to the delocalisation of a lone pair from a planar phosphorus centre into the vacant p‐orbital at arsenic; the bonding in 2 has been probed by DFT calculations. An attempt to synthesise an analogous diphosphaphosphenium salt unexpectedly generated the cyclic phosphonium salt [ cyclo ‐(Mes)P2 P(Mes)2 ][BAr F 4 ]⋅CyMe through the cyclisation of a putative phosphine‐substituted diphosphene cation intermediate. Abstract : The first diphosphaarsenium cation has been synthesised. This cation exhibits remarkable stability because of the delocalisation of a lone pair from a planar phosphorus centre into the vacant arsenic p‐orbital.